Penerapan Laporan Keuangan Berdasarkan SAK EMKM pada UMKM Zhonamood.Shop Kabupaten Blitar - Zumaroh, Hanik; Ni’am, Zaki Bahrun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
MSMEs are an important pillar in the Indonesian economy, because they play an important role in reducing poverty. With the existence of MSMEs, financial reports are important in an effort to provide information about financial conditions. As for the preparation of financial reports, it can refer to SAK EMKM, which is a Financial Accounting Standard prepared by the Financial Accounting Standards Board of the Indonesian Accounting Association. Zhonamood.shop is one of the MSMEs in Blitar Regency which is engaged in the fashion business. The purpose of this study was to find out the application of financial reports according to standards in Zhonamood.shop SMEs. This research method uses descriptive qualitative. Sources of data in the form of primary data, namely interviews and documentation, as well as secondary data in the form of sales records for January, February, march 2023. Data collection techniques use interviews, observation and documentation. From the results of the study, it can be concluded that the SMEs have not implemented the preparation of financial reports in accordance with SAK EMKM due to the owner's lack of understanding regarding financial reports. Therefore, it is hoped that this research will be able to assist Zhonamood.shop MSME owners in implementing good financial reports and in accordance with SAK EMKM. Keywords: MSME, Financial Statements, SAK EMKM